Un proyecto de Gaudi en Chile - Matzner T., Christian (Universidad de Chile. Facultad de Arquitectura y Urbanismo, 1996)
There is a desire to construct a chapel in Rancagua, Chile, which was originally designed for the Sacred Family Temple in Barcelona by Gaudi approved this Project 74 years ago.